Numerical simulation of RF heating heavy oil reservoir based on the coupling between electromagnetic and temperature field. (15th May 2018) - Wang, Zhengxu; Gao, Deli; Fang, Jun
Graphical abstract: Highlights: Heavy oil recovery using RF heating with antenna arrays is demonstrated. Coupled model are presented for electromagnetic heating of heavy oil. The changeable thermo-physical properties of reservoir with temperature can predict accurately the temperature profile. Diminution of sleeve permittivity is a measure of easing high temperature in the vicinity of wellbore. Abstract: At present, a technology of RF (radio frequency) heating is being investigated for enhanced heavy oil recovery, but continued high temperature appears near wellbore, which may destroy the wellbore integrity and RF apparatus. This paper first introduces a novel RF apparatus composed of antenna arrays for heating the heavy oil reservoir, and then the temperature distribution is calculated based on the coupling between electromagnetic and temperature field. To alleviate the high temperature in the vicinity of wellbore, two solutions are proposed: (1) a sleeve made of PTFE (polytetrafluoroethylene) is applied to the outside of the RF apparatus; (2) for improving accuracy of temperature calculation, thermos-physical parameters of reservoir, which are depended on the temperature, are considered specifically in the heat transfer equation and wave equation. Finally, the effect of properties of reservoir and the relative permittivity of sleeve on temperature distribution are investigated. Calculation results indicate that relative permittivity of sleeve has a tremendous influence on temperature distribution, and maximum temperature declines nearby the wellbore as the diminution of relative permittivity, moreover, the positions with highest temperature are moving far from the wellbore. When the parameters of specific heat and thermal conductivity are variable, the maximum temperature near the wellbore is lower than the temperature calculated by constant parameters. Variable relative permittivity of water can't decrease the temperature around the wellbore.